Effect of Cathode Cooling in Three-Dimensional Simulations of an Atmospheric Pressure Glow Discharge - Valentin Boutrouche; Juan Pablo Trelles (Plasma)
The Atmospheric Pressure Glow Discharge (APGD) is a relatively simple and versatile plasma source used in a wide range of applications. Active cooling of the cathode can effectively mitigate instabilities, leading to glow-to-arc transitions. This study investigates the effect of varying the degree of cathode cooling in APGD with a planar cathode in helium. The plasma flow model incorporates mass conservation, chemical species transport, momentum conservation, conservation of thermal energy of heavy species and of electrons, and electrostatics. The model is applied to time-dependent simulations through a three-dimensional computational domain describing the whole discharge, without geometric symmetry or steady-state assumptions. Simulations of an experimentally characterized APGD explore the effects of electric current and cathode cooling—ranging from thermally insulated to extreme convective cooling. Results show the formation of an annular region with high electric field over the cathode surface under conditions of high current and low cooling.